The Effect of Body Weight Variations on Specific Absorption Rate (SAR) Values and Body Temperature in MRI Examination: A Review - Hasbi, Nurul Auliyaa; Amir, Asmiati; Yunus, Muhammad (Jurnal Pijar Mipa, 2025)
MRI examinations use a radiofrequency pulse (RF), which is absorbed by the body when the electromagnetic field is emitted. This is called the specific absorption rate (SAR) effect, which is defined as the heat absorbed per mass of tissue. The type of research uses a systematic literature review or Literature Review with a qualitative approach, with inclusion criteria for publication journals that discuss the effect of body weight on SAR values ​​and changes in body temperature on MRI, as well as journals using retrospective data as clinical and quasi-experimental studies using patients or phantoms. Data processing is carried out by tabulating journals. Data is analysed descriptively and synthesizing research results, the results of which are reported narratively and are systematic, clear, comprehensive, by identifying, analysing, and evaluating through the collection of existing data with explicit search methods and involving a critical review process in selecting studies by aggregating data based on facts with a medical approach. The ten journals the author used have the same results. The results obtained from journals using variations in body weight that are classified as thin body weight (40-49 Kg) have lower SAR values ​​than patients who are classified as normal weight (50-59 Kg) and patients with fat body weight (60-69 Kg) and patients with Obese weight (70-79 Kg) have SAR values ​​far above the SAR value in patients with normal bodies. This proves that body weight will affect the amount of RF absorbed by the body, causing tissue heating, which causes an increase in SAR values. Weight gain can affect the increase in SAR values ​​because the heavier the object, the greater the amplitude of the RF emitted, causing heating in the tissue, causing the SAR value to increase. An increase in body temperature can affect the increase in SAR values ​​because RF absorption will interact with body water molecules to increase movement, equivalent to a rise in energy that will increase body temperature, due to tissue heating. There is an influence of body weight variation on the SAR value which shows that the amount of body weight determines the amount of RF emitted so that the body will absorb a lot, and there is an influence of body weight variation on the increase in body temperature which shows that if the body has a lot of fat, the fat in the subcutaneous tissue can maintain the temperature, both hot and cold and has an effect on RF radiofrequency exposure which adjusts to the surface of the object.